2015
DOI: 10.1177/1932296815587939
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Observational Study of the First-Generation Intravenous Blood Glucose Monitoring System in Hospitalized Patients

Abstract: Background: Current methods of blood glucose (BG) monitoring and insulin delivery are labor intensive and commonly fail to achieve the desired level of BG control. There is great clinical need in the hospital for a user-friendly bedside device that can automatically monitor the concentration of BG safely, accurately, frequently, and reliably. Methods: A 100-patient observation study was conducted at 6 US hospitals to evaluate the first generation of the Intravenous Blood Glucose (IVBG) System (Edwards Lifescie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
(101 reference statements)
0
8
0
Order By: Relevance
“… As each new study is published, we learn more about how current systems can be improved. For example, a recent study reporting on the safety, accuracy, and reliability of an intravenous blood glucose system demonstrated that more than half of the sensors inserted had to be removed before the end of the planned 72-hour study period [ 59 ]. Similarly in a RCT comparing the use of subcutaneous CGM with frequent point-of-care measurements, only 177 of the 1954 patients initially screened were finally included [ 60 ].…”
Section: Moving Forward … and How To Keep The Industry On Board?mentioning
confidence: 99%
“… As each new study is published, we learn more about how current systems can be improved. For example, a recent study reporting on the safety, accuracy, and reliability of an intravenous blood glucose system demonstrated that more than half of the sensors inserted had to be removed before the end of the planned 72-hour study period [ 59 ]. Similarly in a RCT comparing the use of subcutaneous CGM with frequent point-of-care measurements, only 177 of the 1954 patients initially screened were finally included [ 60 ].…”
Section: Moving Forward … and How To Keep The Industry On Board?mentioning
confidence: 99%
“…The first-generation intravenous CGMS was evaluated in a multicenter observational study, in 100 critically-ill patients (43). The authors concluded that it was easy to set up and use, attached to a peripheral venous catheter.…”
Section: Poc Continuous Glucose Monitoring Systems (Cgms) In Diabetesmentioning
confidence: 99%
“…Of the intravenous glucose monitoring measurements, 93% met the 2003 ISO Standards for accura- cy. Frequent and accurate POC blood glucose testing may improve the safety and efficacy of insulin therapy and blood glucose control in hospitalized patients (43). A randomized controlled trial compared subcutaneous CGMS with frequent POC measurements in 156 critically ill patients (42).…”
Section: Poc Continuous Glucose Monitoring Systems (Cgms) In Diabetesmentioning
confidence: 99%
“…Obstruction of venous blood flow by thrombus may cause reaspiration of flush solution and a preanalytical dilution error. [112][113][114][115] The OptiScanner® (OptiScan, Inc, Hayward, CA, USA ) is CE Mark approved for monitoring the concentration of plasma glucose in blood sampled from the proximal port of a CVC every 15 minutes for 72 hours. The CGMS automatically transports a small sample of blood from the CVC to a bedside monitor that contains a centrifuge, spectrometer, and data display.…”
Section: Vascular Catheter Blood-sampling Cgms For Hospitalized Patientsmentioning
confidence: 99%
“…Obstruction of venous blood flow by thrombus may cause reaspiration of flush solution and a preanalytical dilution error. 112-115…”
Section: Vascular Catheter Blood-sampling Cgms For Hospitalized Patientsmentioning
confidence: 99%